Sistem Informasi Perpustakaan Berbasis Web SMAN 18 Jakarta Utara - Swastika, Rahayu; Akhromi, Ahmad; Mawanti, Iis; Velany, Mellamel (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2021)
In a system that has been designed and has been realized in an information system program, it will certainly continue to implement activities on the system. With advances in all fields, all kinds of ways to store this data can be done with a computer, or what is commonly known as computerization. So that the information system that the author is creating is a web-based library information system, in this system all data and library transaction activities are computerized. The process of implementing this web-based information system will be carried out at Senior High School, SMAN 18 North Jakarta, which is located in the North Jakarta area, especially in the Warakas area. Because the library facilities at this school still use a system that is still manual by only recording borrowing data and book data only in a transaction book and this has led to data manipulation in the process of borrowing and returning transactions. The methods that I use in developing devices, using the waterfall method are: Software Requirements Analysis, Design, Code Generation, Testing, and Support or Maintenance, while for Data collection techniques are by observing the library transaction process at SMAN18, conducting interviews with library staff and literature studies. After developing the information system for the library services at SMAN 18 North Jakarta, the library has undergone improvements and changes to the system, has become more effective and efficient and more conducive, the management method has become better, namely from manual system processes to computerized and increased data security, as well as systems. This management, users can access through the website anywhere and anytime to see ongoing transactions and view library book data.